Adsorption of methylene blue and malachite green on micro-mesoporous carbon materials - K Jedynak; M Repelewicz (Adsorption Science & Technology)
The aim of this work was to investigate the determination of adsorption kinetics and adsorption isotherms for methylene blue (MB) and malachite green (MG) from aqueous solutions, on micro-mesoporous carbon materials, C–HA, C–HA–CO 2 , C–CA and C–CA–CO 2 , obtained by soft-templating method. In most cases, the adsorption kinetics proceeded in compliance with pseudo II-order reaction model, only in one case with pseudo I-order reaction model: C–CA (MG). Adsorption, in equilibrium conditions, was described by Langmuir and Freundlich equations. In five cases, the adsorption proceeded in compliance with the Langmuir model: C–HA (MB, MG), C–HA–CO 2 (MB, MG), C–CA–CO 2 (MB); in three cases, the adsorption was described using Freundlich equation: C–CA (MG, MB), C–CA–CO 2 (MG).